1995
DOI: 10.1143/jjap.34.l145
|View full text |Cite
|
Sign up to set email alerts
|

Observation of 7×7 Reconstructed Structure on the Silicon (111) Surface using Ultrahigh Vacuum Noncontact Atomic Force Microscopy

Abstract: Unlike ultrahigh vacuum (UHV) scanning tunneling microscopy (STM), the effectiveness of UHV in UHV atomic force microscopy (AFM) has not been verified. Intensive interaction between tip and sample in UHV often damages the sample surface in the contact mode. Although noncontact (NC) AFM is effective in protecting the sample surface, it has failed to provide atomic-level resolution. We used a stiff silicon cantilever ( ∼40 N/m) capable of STM imaging, and succeeded in obtaining the first atomic-resolution images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(144 citation statements)
references
References 9 publications
4
138
0
2
Order By: Relevance
“…FM-AFM has been used mainly for atomic-scale imaging in ultrahigh vacuum [14,15], and its application in liquid has been very limited [16]. Recently, it has become possible to obtain true atomic resolution with piconewton order loading forces even in liquid [17] using an ultralow noise cantilever deflection detection system [18], enabling extremely small amplitude cantilever oscillations [19].…”
Section: Direct Imaging Of Lipid-ion Network Formation Under Physiolomentioning
confidence: 99%
“…FM-AFM has been used mainly for atomic-scale imaging in ultrahigh vacuum [14,15], and its application in liquid has been very limited [16]. Recently, it has become possible to obtain true atomic resolution with piconewton order loading forces even in liquid [17] using an ultralow noise cantilever deflection detection system [18], enabling extremely small amplitude cantilever oscillations [19].…”
Section: Direct Imaging Of Lipid-ion Network Formation Under Physiolomentioning
confidence: 99%
“…6 FM-AFM with large amplitudes has made it possible recently to achieve atomic resolution of even reactive surfaces in ultrahigh vacuum. The silicon ͑111͒-͑7ϫ7͒ reconstruction, [7][8][9][10][11][12] defects on InP, 13 and insulating surfaces 14,15 have been imaged by FM-AFM. It has been found that A 0 has to be very large compared to the range of F ts for obtaining optimal resolution, therefore the connection between f and F ts is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial AFM cantilevers (Budget Sensors and Micro Masch) covered by platinum were used. The cantilever deflection sensor is based on the optical lever principle [27,28]. The beam of a small semiconductor laser with feedback-controlled output power (SPMC01, Power Technologies Inc., 1 mW at 670 nm) is focused onto the back side of the cantilever.…”
Section: Cantilever Control Assemblymentioning
confidence: 99%